Reception material in the Ingmar Bergman Archives: Letters, essays, drawings. Issue 2 (1st June 2014) - Hanssen, Eirik Frisvold
This article considers documents relating to two different sections of the Ingmar Bergman Archives, emphasizing some of the social and cultural characteristics of the material. Analysis of letters from ordinary film spectators constitutes one portion. Another concerns Bergman's employment as manager and director of the municipal children's theatre Sagoteatern (The Fairy-Tale Theatre) in Stockholm (1941–1942). In both cases, the auteur archive becomes a site for examining the spectator rather than the auteur. The article examines how the chosen material may convey knowledge about spectatorship, and specific social and personal experiences of cinema and theatre, by making visible a range of cultural practices seldom associated with auteurism or 'film art', which nonetheless can be incorporated in an auteur archive.